K.H. A. WAHID HASYIM DAN KONSEP PENDIDIKAN ISLAM - Samsul Hadi (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2014)
The discourse on Islamic education has always been an interesting study not only because of the education has distinctive features (characteristics) of its own, but also because of the rich Islamic education with the concept of educational thoughts were not inferior quality compared to modern educational concepts. We may encounter in the treasure of Islamic educational thought leaders with some clever ideas, creative and innovative in providing alternative unique nuances of Islamic education, which bridges the gap dichotomy of general science and the science of religion, especially in education at the school. They are able to be inspiration, contributors, even the executor of the dynamic development of Islamic education in Indonesia, especially in the world pesantren. Pesantren is one of the oldest institutions of Islamic education in Indonesia, which has a significant contribution in educating the nation. Viewed historically, the Boarding School has tremendous experience in developing, educating and developing the surrounding community Boarding School is a unique educational institution not because of the long existence, but also culture methods and networks established by the religious institutions